Measurement of colour development in Pinus radiata sapwood boards during drying at various schedules - McCurdy, Murray; Pang, Shusheng; Keey, Roger (Maderas. Ciencia y Tecnología, 2014)
Colour changes, such as kiln brown stain, that develop in Pinus radiata boards during kiln drying can reduce the value of the final wood products and result in significant losses due to downgrade or waste of dried wood by removing the darkened surfaces. This study measured how colour developed in Pinus radiata sapwood boards under different drying schedules. The boards used in these experiments were 40x100x800mm, cut from the same log and were endand edge-matched. Boards were dried at eight different schedules using temperatures from 50°C to 120°C and relative humidities from 14% to 67%. Separate boards were dried for 5 equal intervals through each schedule and colour profiles measured through the boards using a surface reflectance spectrophotometer. Lightness, L*, on a greyscale was used as an indication of colour change (darkening). The results show that there is generally a greater decrease in lightness with higher temperature schedules and also with slower, higher relative humidity, schedules. This suggests that both temperature and drying time are significant factors in the formation of colour during drying. The most significant changes in colour occurred near the board surfaces, indicating kiln brown stain.